Web-Based Room Loan Management Services Using Web Based RAD Method: Web-Based Room Loan Management Services Using Web Based RAD Method - Upi Resti Wahyuni; Fauziah Fauziah; Eri Mardiani (Institute of Computer Science (IOCS), 2020)
At the moment, the information service System in every campus is very important, and students are also currently enthusiastic to conduct activities on campus by utilizing the facilities provided by the campus, therefore it is necessary to do to design the information system of lending management services through the website, because the current system is still manual, which is the user of the room in the process is still done by meeting the administrator This requires a relatively long process that makes it difficult for users and administrators. Then in the data logging of the room that has not been integrated into a system will complicate the administrator if you want to give access to the user room. The method for designing the application uses the RAD (Rapid Application Development) method. RAD is a model of the software development process that belongs to the incremental technique (multilevel), the RAD method used is iterative (recurring) in developing the system, in the creation of the RAD model that works, in the development stage set the need (requirement). The stages of creating this Web application utilize PHP and Mysql. From the results of this research user and the user can easily manage the management of room lending.